Supraventricular cardiac conduction system exposure in breast cancer patients treated with radiotherapy and association with heart and cardiac chambers doses. (January 2023) - Errahmani, M.Y.; Locquet, M.; Broggio, D.; Spoor, D.; Jimenez, G.; Camilleri, J.; Langendijk, J.A.; Crijns, A.P.G.; Bernier, M.O.; Ferrières, J.; Thariat, J.; Boveda, S.; et al.
Highlights: Dosimetry of SAN and AVN during breast cancer irradiation is poorly known whereas it may enhance knowledge on radiation-associated supraventricular cardiac conduction disease. For right-sided breast cancer treated with 3D-CRT, SAN dose could exceed several grays, in contrast with lower doses for AVN. The right atrium may be an interesting surrogate for SAN dose, but AVN dose is more complicated to predict with large cardiac structures. SAN and AVN delineations remain necessary to precisely evaluate conduction nodes exposure. Abstract: Purpose: To assess sinoatrial node (SAN) and atrioventricular node (AVN) doses for breast cancer (BC) patients treated with 3D-CRT and evaluate whether "large" cardiac structures (whole heart and four cardiac chambers) would be relevant surrogates. Material and methods: This single center study was based on 116 BCE patients (56 left-sided, 60 right-sided) treated with 3D-CRT without respiratory gating strategies and few IMN irradiations from 2009 to 2013. The heart, the left and right ventricles (LV, RV), the left and right atria (LA, RA) were contoured using multi-atlases for auto-segmentation. The SAN and the AVN were manually delineated using a specific atlas. Based on regression analysis, the coefficients of determination (R 2 ) were estimated to evaluate whether "large" cardiac structures were relevant surrogates (R 2 > 0.70) of SAN and AVN doses. Results: For left-sided BC, mean doses were: 3.60 ± 2.28 Gy for heart, 0.47 ± 0.24 Gy for SAN and 0.74 ± 0.29 Gy for AVN. For right-sided BC, mean heart dose was 0.60 ± 0.25 Gy, mean SAN dose was 1.57 ± 0.63 Gy (>85 % of patients with SAN doses > 1 Gy) and mean AVN dose was 0.51 ± 0.14 Gy. Among all "large" cardiac structures, RA appeared as the best surrogate for SAN doses (R 2 > 0.80). Regarding AVN doses, the RA may also be an interesting surrogate for left-sided BC (R 2 = 0.78), but none of "large" cardiac structures appeared as relevant surrogates among right-sided BC (all R 2 < 0.70), except the LA for patients with IMN (R 2 = 0.83). Conclusions: In BC patients treated 10 years ago with 3D-CRT, SAN and AVN exposure was moderate but could exceed 1 Gy to the SAN in many right-sided patients with no IMN-inclusion. The RA appeared as an interesting surrogate for SAN exposure. Specific conduction nodes delineation remains necessary by using modern radiotherapy techniques.